2015
DOI: 10.1016/j.ygyno.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiling of ascites at primary surgery identifies an interaction of tumor necrosis factor-α and interleukin-6 in predicting reduced progression-free survival in epithelial ovarian cancer

Abstract: Objectives Epithelial ovarian cancer (EOC) typically presents with advanced disease. Even with optimal debulking and response to adjuvant chemotherapy, the majority of patients will have disease relapse. We evaluated cytokine and chemokine profiles in ascites at primary surgery as biomarkers for progression-free survival (PFS) and overall survival (OS) in patients with advanced EOC. Methods Retrospective analysis of patients (n =70) who underwent surgery at Roswell Park Cancer Institute between 2002-12, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 34 publications
3
52
0
2
Order By: Relevance
“…We observed that the combination of high levels of IL-6 and TNF-α in ascites of patients with newly diagnosed epithelial ovarian cancer predicted worse outcome [28]; however, this was a small single-center study, and cytokine profiling from other centers have produced different results [29]. In addition to stimulating thrombocytosis, IL-6 within the tumor microenvironment can have broad effects on tumor, inflammatory, and non-immune stromal cells, including increasing endothelial cell permeability that drives ascites generation [30].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the combination of high levels of IL-6 and TNF-α in ascites of patients with newly diagnosed epithelial ovarian cancer predicted worse outcome [28]; however, this was a small single-center study, and cytokine profiling from other centers have produced different results [29]. In addition to stimulating thrombocytosis, IL-6 within the tumor microenvironment can have broad effects on tumor, inflammatory, and non-immune stromal cells, including increasing endothelial cell permeability that drives ascites generation [30].…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic factors for advanced epithelial ovarian cancer principally rely on age, performance status, residual tumor volume following primary surgery, and tumor histology (Kolomeyevskaya et al 2015). It has been shown that substantial variability in progression-free survival exists among women with similar disease stage (Kolomeyevskaya et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that substantial variability in progression-free survival exists among women with similar disease stage (Kolomeyevskaya et al 2015). The accessibility of ascites composition could provide an opportunity to identify prognostic and treatment-monitor markers (Ahmed and Stenvers 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, cytokines present in the post-ovulatory ovaries such as IL-6, IL-8, CCL2/MCP-1 and CCL5/RANTES have been demonstrated to modulate ovarian cancer (Freedman et al 2004). These factors have been shown to induce in vitro growth of ovarian cancer cell lines, induce expression of angiogenic factors such as VEGF and inversely correlate with patient survival (Kolomeyevskaya et al 2015, So et al 2015, Eichten et al 2016.…”
Section: Seeding and Establishment In The Ovaries: Role Of The Ovariamentioning
confidence: 99%